(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Due to the ever-growing demand for energy and the continuous depletion of conventional oil reserves, the petroleum industry is faced with the challenge of recovering more hydrocarbons from existing reservoirs. Enhanced Oil Recovery (EOR) technologies have emerged as effective methods to increase oil production beyond primary and secondary recovery stages. Among the various EOR techniques, the use of nanofluids—especially those containing silica (SiO₂) and alumina (Al₂O₃) nanoparticles—has shown great promise. These nanofluids improve oil recovery by altering rock wettability, decreasing interfacial tension (IFT), and improving fluid mobility. This study focuses on assessing how temperature variations affect the stability of hybrid nanofluids and their subsequent impact on oil recovery performance. Through comprehensive visual testing and injection into 2D micromodels saturated with crude oil, results demonstrate that elevated temperatures enhance nanoparticle stability, leading to more efficient oil displacement. The findings suggest that hybrid nanofluids could provide a superior EOR strategy for high-temperature reservoir environments.